Avaliação in vitro da atividade antimicrobiana da terapia fotodinâmica sobre Streptococcus mutans em biofilme denteal in situ - Panhóca, Vitor Hugo (2011)
The Photodynamic Antimicrobial Chemotherapy (PACT) has shown that is a promising alternative for buccal disinfection. The objective of this in situ work is to investigate the antimicrobial effect of photodynamic therapy over biofilms by the use of curcumine and Photogem® presented in a solution. In this research 18 volunteers were selected randomly from both sexes, with age over than 18 years. These patients wore a removable palatine device that contained six enamel/dentin specimens of 5 square millimeters by 2 millimeters of thickness. Those patients wore those devices during the period of four days, after that the biofilm created over the specimens were treated using different PACT protocols. The effect of the PACT treatments was evaluated by the microbial reduction of the Streptococcus mutans by UFC counting. This study compared a control group with the curcumine group that didn't received light irradiation with another group that was treated with the PACT protocol using curcumine solution, and other group that used the photosensitizer presented in solution with Photogem®. The obtained results of this investigation showed the reduction of the amount of the S. mutans UFC. The highest reduction (p=0.02) was observed when the PACT is applied with solution using Photogem as the photosensitizer. In conclusion, this study suggests that there is a antimicrobial effect of photodynamic therapy over biofilms by the use of curcumine (1.500μg/mL) and Photogem® (1.000μg/mL) followed by LED system irradiation (λ=640±5nm).